MEMBANGUN APLIKASI WEB FRONT END DENGAN TEKNIK JSON (JAVA SCRIPT OBJECT NOTATION) - Joko Triyono; Prita Haryani; Muhammad Farid Ali Sa’fii (IST AKPRIND Yogyakarta, 2018)
The development of technology has become very extraordinary, in the era of 4.0, the information technology sector has become a very important part in every activity or work. In web-based programming techniques also undergo significant changes, JSON (Java Script Object Notation) is one of the data management techniques that will change the DBMS (Database Management Systems) paradigm in terms of design and implementation. Likewise in terms of process speed, JSON offers a very tempting speed, combined with local storage on HTML5. Of course these developments will also affect the need for information so that the addition of modules and / or facilities in the information system must certainly be done without disturbing the existence of information systems that are currently running. Modular systems become things that need to be considered in the development of information systems, with a modular system that allows developers to work in parallel at different places at the same time without having to wait for each other, sharing databases is not a problem for now. The result of this research is a technique in building a web front end by using JSON technique as a data provider and implemented with HTML5 and PHP, by embedding it on the server side with database and Server side on Client as a link between systems. So that obtained a presentation of information on a web application on the client without connecting to the database directly. The client is built in addition to using PHP / Web-based applications and can also use Android-based applications.